Regional Economic Development Analysis and Planning Strategy - Stimson, Robert J.; Stough, Roger R.; Roberts, Brian H. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The second edition of this book is completely reedited making the book even more valuable for graduate students, reflecting recent advances and adding insightful new material. The book is about the analysis of regional economic performance and change, and how analysis integrates with strategies for local and regional economic development policy and planning. First, the book provides the reader with an overview of key theoretical and conceptual contexts within which the economic development process takes place. However, the deliberate emphasis is to provide the reader with an account of quantitative and qualitative approaches to regional economic analysis and of old and new strategic frameworks for formulating regional economic development planning. The second edition brings to the present its original thesis about the need for regions to be fast and flexible, but also to be proactive in order to be prepared to experience increasingly greater shocks while having less time to adjust their economic development to achieve sustainability. This is underscored by events that have occurred since 2001: 9/11 terrorist attacks, continuing rapid advances in technology, the rise China and India, the Tsunami, and all the known on-going and unforeseen risks and challenges that confront nations around the globe and the regions and localities within them. The book presents strategies and the traditional and expanded methods used to create and implement them.